China’s Unsubstantiated Claims on Baselines - Nguyen, Thi Kim Cuc; Ngo, Huu Phuoc (Lentera Hukum, 2023)
For all nations, the stability of the global order is a significant concern. Despite the efforts of the international community, Asia’s peace and security are threatened by China’s aggressive behaviours in the South China Sea. Accordingly, China has claimed nearly the whole South China Sea as its territory, including water internationally acknowledged as belonging to other nations. States have the right to determine and declare their baselines for coastal areas, islands, and archipelagos that fall under their national sovereignty with regard to international law of the sea. Because of the inconsistency with the rules of international law in general and the international law of the sea in particular, China’s claims in this case are unsubstantiated. This article aims to determine China's violations to comply with their obligations under international law, especially in the South China Sea disputes. By using analysed and evaluated methods, this study pointed out the regulations that violate international law contained in documents such as the Declaration of China on the baselines of the territorial sea in 1996, the Coast Guard Law of China in 2021, the Maritime Traffic Safety Law of China in 2021, by using the comparative methods of these documents with the provisions of the international law, particularly the United Nations Convention on the Law of the Sea in 1982. The article also highlights the severe effects of China's behavior on Vietnam, particularly the implementation of the two laws previously mentioned that violate Vietnam's territorial integrity in the Paracel and Spratly Islands. As a result, the paper suggests certain notes for Vietnam and other nations to void China’s aforementioned legal documents. These suggestions, in particular, will contribute to protecting the sovereignty, sovereign rights, and jurisdiction of Vietnam, and the freedom of navigation and overflight of countries for nations across the world.Keywords: International Law, International Security, South China Sea.